2021
DOI: 10.3390/biom11111595
|View full text |Cite
|
Sign up to set email alerts
|

The Odorant Binding Protein, SiOBP5, Mediates Alarm Pheromone Olfactory Recognition in the Red Imported Fire Ant, Solenopsis invicta

Abstract: Olfaction is crucial in mediating various behaviors of social insects such as red imported fire ants, Solenopsis invicta Buren. Olfactory receptor (OR) complexes consist of odor-specific ORs and OR co-receptors (Orco). Orcos are highly conserved across insect taxa and are widely co-expressed with ORs. Odorant binding proteins (OBPs) can transport semiochemicals to ORs as protein carriers and thus constitute the first molecular recognition step in insect olfaction. In this study, three OBP genes highly expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…On the contrary, undecane elicited a weak EAG response in the control fire ants, but Cd exposure significantly activated the EAG response after two, four, and 6 weeks (Figure D). The alkaloid, 2,4,6-trimethylpyridine, from the lady beetle, was previously demonstrated to evoke strong EAG responses in S. invicta . , However, exposure to 100 mg Cd kg –1 for 2 weeks deprived the EAG response to this odorant . Analogously, the electro-olfactogram (EOG) responses of goldfish to food-related odorants and postovulatory pheromone were weakened after 10 min exposure to 0.1 mM copper sulfate .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…On the contrary, undecane elicited a weak EAG response in the control fire ants, but Cd exposure significantly activated the EAG response after two, four, and 6 weeks (Figure D). The alkaloid, 2,4,6-trimethylpyridine, from the lady beetle, was previously demonstrated to evoke strong EAG responses in S. invicta . , However, exposure to 100 mg Cd kg –1 for 2 weeks deprived the EAG response to this odorant . Analogously, the electro-olfactogram (EOG) responses of goldfish to food-related odorants and postovulatory pheromone were weakened after 10 min exposure to 0.1 mM copper sulfate .…”
Section: Resultsmentioning
confidence: 97%
“…Although the sequences encoding putative OBPs in S. invicta have been identified and the temporal and spatial expression of SiOBPs has been profiled, the functions of SiOBPs in semiochemical detection of S. invicta remain largely unknown. A previous study reported that SiOBP5 is crucial for the perception of 2-ethyl-3,5(6)-dimethylpyrazine, the alarm pheromone of S. invicta . To explore the function of SiOBP7 and SiOBP15 in the olfactory perception of S. invicta , we determined the behavioral responses of fire ants to these odorants with higher binding affinities after knocking down SiOBP7 or SiOBP15.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity in Or49a is carried on by PNs to the lateral protocerebrum, which behaviourally mediates the avoidance behaviour of adult flies [ 6 ]. Similarly, a recent study showed that specific odorant-binding proteins mediate the olfactory recognition of the alarm pheromone in the fire ant Solenopsis invicta [ 112 ]. Also, the “flee” response observed in aphids that drop from their host plant when detecting either the predator or the alarm pheromone from conspecifics is initiated by a single compound [ 52 ].…”
Section: Neurobiology Of Olfactory Coding For Defensive Mechanisms In...mentioning
confidence: 99%
“…Together, these data are consistent with a combination of the carrier and presentation models for OBP function and implicate a direct interaction between the LUSH and Or67d–Orco pheromone receptors on the dendrites. Following these studies, many groups have demonstrated specific roles for OBP members in the detection of volatile ligands in many species [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ], and even for tastants and humidity [ 89 , 90 ]. Finally, in Drosophila , an odorant-binding protein has been implicated in blocking sugar taste detection when sucrose is present with bitter compounds [ 91 ].…”
Section: Odorant-binding Proteins (Obps)mentioning
confidence: 99%